Exploring kinematic bifurcations and hinge compliance for in-hand manipulation: how could thick-panel origami contribute? - Liu, C; He, L; Wang, S; Williams, A; You, Z; Maiolino, P (Wiley, 2024)
Origami-inspired mechanisms have found significant applications in end effector design. So far, the exploration of thick-panel origami has been relatively limited, but it is worth noting that the incorporation of rigid thick panels can introduce unique mechanical properties, showcasing great potential in addressing manipulation challenges. Our previous work has developed a gripper from thick-panel waterbomb origami, which can pick up a variety of daily objects. Based on the same prototype, this article extends the gripper's function from grasping to in-hand manipulation, which is attributed to the kinematic bifurcations and compliance of thick-panel origami. A kinematic study is carried out to investigate the gripper's bifurcated motion modes. The hinge compliance is also taken into account to enhance the gripper's motion dexterity. Theoretical analysis and experiments are conducted to demonstrate both features, thereby paving the foundation for achieving dexterous motions with a simplified control strategy. Aided by a differential mechanism, the gripper can effectively interact with objects with the actuation inputs from only two motors. Objects including balls, cuboids, and cones are explored for in-hand manipulation under different motion modes, showing varied trajectories. With the integration of tactile sensors at the fingertips, we have also revealed the gripper's potential for classification tasks.